PENGARUH KUALITAS LAPORAN KEUANGAN TERHADAP PERENCANAAN ANGGARAN PADA DINAS PENDIDIKAN KOTA BANDUNG - Heldi Heldi (Sekolah Tinggi Pariwisata Mataram, 2020)
Bandung City Education Authority is a regional unit working that uses the regional expenditure budget to meet its needs in the education sector. But that uses the regional expenditure budget within five years, Bandung City Education Authority is still not optimal in planning budget and realizing the budget. Looking at budget planning and budget realization that has not been optimal, this is thought to be influenced by the quality of financial reports produced by the Bandung City Education Authority in the previous period. The purpose of this study is to find out how munch influence the financial statements are relevant, reliable, comparable and understandable to budget planning of Bandung City Education Authority. The author uses the quality of financial statement theory (variable X) from Suwanda which consist of four dimensions is the financial statements that are relevant, the financial statement reliable, the financial statement can be compared, and the financial statement can be understand. While for the budget planning theory (variable Y) the author uses the theory from Bastian which consist of three dimensions is planning long term, medium term, and short term planning. The method used in this research is a quantitative method whit an associative approach. Data collections techniques used this research were library studies, observations, and direct questionnaires to respondents with 30 respondents and using saturated sampling techniques. The analysis technique used is simple regression test, multiple regression test, correlation coefficient test, F test, T test, and determination test that uses SPSS 17. The results of the research concluded that financial statement that are relevant, reliable, comparable, and can be understood simultaneously have an effect on budget planning of the Bandung City Education Authority. In the F test the results F count of 121.047 and F table of 2.98. Meaning F count is greater than F table (121.047 > 2.98). With a determination coefficient of 95,1% and the remaining 4,9% is influenced by other factors not examining